Legal Consequences Dispute Settlement Body Decision 477-478 Concerning Protection and Empowerment of The Farmers - Sihnomo Abu Hilmy (Susbtantive Justice International Journal of Law, 2020)
Agriculture has an important role in providing food for the community. The Increasing of open world trade, especially in food products, causes prices of domestic food products to be affected by the situation and conditions of international food prices. To protect farmers, the Law Number 19 of 2013 concerning Protection and Empowerment of Farmers has been enacted. In the implementation of the law, especially Article 30 Paragraph (1), received many complaints from Indonesian trading partners, such as the United States and New Zealand who stated that these rules were inconsistent with the GATT provisions. The research method in writing this journal is a normative juridical approach method. In summary, the conclusions from the results of the first discussion, the protection of farmers in addressing world trade is regulated in Article 30 Paragraph (1) of the article aimed at protecting farmers as food producers from loss of price risk due to uncontrolled import of agricultural commodities. Second, Responding to the DS 477-478 WTO ruling it is necessary to revise Article 30 Paragraph (1) because it is contrary to the principle of quantitative restrictive prohibition. Changes to the article should still be used as an instrument to protect farmers as food producers by harmonizing the provisions contained in the WTO